Modified delphi technique: the future of vocational learning skills - Nashir, Irdayanti Mat; Yusoff, Abdullah; Ma’arof, Nurul Nazirah Imam; Ismail, Mohamad Amiruddin; Khairudin, Moh; Andriani, Dwi Esti; Idris, Muhammad Ridzuan; Sudiyatno, Sudiyatno (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2021)
This article explains the development of checklist which is related with future of vocational learning skills by using the Modified Delphi techniques. The Modified Delphi technique provides the opportunity for researchers to gather input from participants in the first round of collecting data and then distributed that checklist to the expertise until consensus achieved. Often, the process is used to find consensus among experts who have different views and perspectives. The Modified Delphi technique enables group problem-solving using an iterative process of problem definition, discussion, feedback, and revisions. This paper will discuss the basics of the Modified Delphi techniques, its application potential, the selection of expert panels and the means on how consensus can be reached among the participants using examples of our past research using the technique. The 13 out of 15 domain of the future learning skills have found in this research.